2014
DOI: 10.1016/j.febslet.2014.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Transportin‐1 and Transportin‐2: Protein nuclear import and beyond

Abstract: Edited by Ulrike KutayKeywords: Transportin Importins Karyopherins Nuclear import Nucleo-cytoplasmic transport NLS Kap104p Transportin-1 Transportin-2 Karyopherin-b2 hnRNP A1 FUS a b s t r a c t Nearly 20 years after its identification as a new b-karyopherin mediating the nuclear import of the RNA-binding protein hnRNP A1, Transportin-1 is still commonly overlooked in comparison with its best known cousin, Importin-b. Transportin-1 is nonetheless a considerable player in nucleo-cytoplasmic transport. Over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 136 publications
(228 reference statements)
4
95
0
Order By: Relevance
“…2B). Originally proposed to mediate bidirectional transport, more recent studies maintain that transportins 1 and 2 are restricted to mediating nuclear import of RNA-binding proteins that function as splicing regulators (Twyffels et al, 2014). Therefore, we predicted that the transportins would not be involved in TRα1 shuttling.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Originally proposed to mediate bidirectional transport, more recent studies maintain that transportins 1 and 2 are restricted to mediating nuclear import of RNA-binding proteins that function as splicing regulators (Twyffels et al, 2014). Therefore, we predicted that the transportins would not be involved in TRα1 shuttling.…”
Section: Resultsmentioning
confidence: 99%
“…However, several technical obstacles have rendered the systematic mapping of cargo–NTR relationships challenging: (i) The transient nature of cargo–NTR interactions makes them largely inaccessible to biochemical identification by NTR‐centric affinity purification; (ii) each NTR does recognize a multitude of cargos and their cargo spectrum might overlap; and (iii) cargo abundances (copy numbers per cell) span several orders of magnitude in situ . The vast majority of previous studies therefore were designed in a cargo‐centric manner and have reported transport pathways for individual cargos (for review, see, e.g., Chook & Süel, 2011; Kimura & Imamoto, 2014; Twyffels et al , 2014). Although powerful for studying the contribution of the nuclear transport system to individual cellular mechanisms, these approaches are not suitable to comprehensively chart its cargo spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the differences in the critical HEAT repeats between IPO3 and TRN1 could be responsible for the differential interaction with NEMO. Whereas well established cargos for TRN1 and IPO3 are involved in RNA metabolism (48), NEMO represents a unique cargo of IPO3 in a non-RNA processing pathway, thereby identifying genotoxic stress-induced NF-B signaling as an important biological pathway regulated by IPO3, not shared by TRN1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, co-crystal structure analysis demonstrated that TRN1 (transportin 1, TNPO1, IPO2) makes extensive contacts with nonclassical NLS sequences known as the proline-tyrosine-NLS (PY-NLS) spanning 30 -40 amino acids via its HEAT repeat motifs (46,47). The sequence model suggested that the PY-NLS motif is present in potentially over 80 distinct proteins (47,48). TRN1 also recognizes cargos that do not have PY-NLS motifs (48), further diversifying the number of substrates it can recognize.…”
mentioning
confidence: 99%
See 1 more Smart Citation